Pricing policies as a marketing strategy in the construction industry: case study of turkish companies - Coskun, Hilmi; Erdis, Ercan; Demirci, Mustafa (Technological and Economic Development of Economy, 2014)
The firms in the construction industry have to determine pricing and promotion policies, then these policies must be carefully and systematically integrated with the marketing strategies. Not only the demand and cost are important in pricing decisions but competition is also a significant variable to be considered. To determine the difficulties and the affecting factors in applying pricing decisions within the marketing concepts in construction sector, a survey was carried out among the Turkish companies as a sample group. In total 49 companies, mostly medium-size firms have been surveyed. The responses of firms are considered based on their actively engaged subsectors, namely, residential, commercial/public buildings, and infrastructure construction. The answers of firms are also evaluated based on their stated organizational structure, namely, simple, hierarchical, project, and network. The views about the various aspects of pricing policy development in phases, for example before and during bid, differ in the construction companies depending on their actively involved fields and their organizational structures.